2003
DOI: 10.1186/1477-7819-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane fatty acid profile and saturation index in gallbladder carcinogenesis: a case-control study

Abstract: BackgroundGallbladder cancer is a common neoplasm of biliary tract, with an unknown etiology.Patients and methodsThis study was carried out to evaluate the changes in the membrane fatty acid profile and saturation index in patients with gallbladder cancer. The study sample consisted of 50 newly diagnosed cases of gallbladder cancer and 50 patients undergoing cholecystectomy for cholelithiasis were recruited as controls. The fatty acid estimation was carried out by high performance liquid chromatography (HPLC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The study of fatty acids extracted from cell membranes is considered a valid approach to evaluate the possible effects of natural compounds on cell morphological changes that can influence the different aspects of tumorigenesis [10,[19][20][21][22]. In this work, we found that GSEs are able to inhibit cell migration in both human colorectal cancer cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The study of fatty acids extracted from cell membranes is considered a valid approach to evaluate the possible effects of natural compounds on cell morphological changes that can influence the different aspects of tumorigenesis [10,[19][20][21][22]. In this work, we found that GSEs are able to inhibit cell migration in both human colorectal cancer cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 72%
“…In this work, we have demonstrated the ability of these two table grape varieties to modify the fatty acid profile of cell membranes and the lipids play certainly an important role in the adaptation of cancer cells [7,20]. The treatment with both varieties of GSEs resulted in a reduction in the total levels of SCD1 in the two cell lines studied, given by the sum of the ratios palmitoleic acid/palmitic acid and oleic acid/stearic acid.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The lipidomic analysis on the erythrocyte membrane as “reporter” for liver injury is well recognized [ 1 , 111 ]. The morphology, permeability, and fluidity, as well as the membrane fatty acids composition of red cell blood and hepatocytes, are very similar [ 1 ].…”
Section: Nafld and Lipidomic Analysismentioning
confidence: 99%
“…Unsaturated lipids, such as oleic acid, determine the decrease of membrane lipid packing, consequently improving fluidity. In this context, the saturation index, SI, and the C18:0/C18:1 ratio, also considered a marker of cell membrane fluidity, gain significance [34,35]. In some epidemiological studies, the ratio of MUFA to SFA has been used to reflect stearoyl-CoA desaturase (SCD) activity as a predictive marker of breast cancer risk [36,37].…”
Section: Introductionmentioning
confidence: 99%